Quality retention of fresh-cut pepper as affected by atmosphere gas composition and ripening stage - Rodoni, Luis Maria (2015)
The responses of fresh-cut (FC) vegetables to CO2 and O2 levels depend on their ripening stage and degree of processing. In this work we evaluated the effect of storage under different CO2 (2.5; 5; 10 and 15 kPa) and O2 (2.5 and 5 kPa) combinations or air on quality retention of FC green and red pepper. Atmospheres with 15 kPa CO2 caused physiological injury at both ripening stages. Red pepper strips were less tolerant to CO2 enrichment within the range 5e10 kPa. Ripe FC peppers were also more sensitive to O2 reductions below 5 kPa. Marked benefits were obtained at both ripening stages with 5 kPa O2 þ 5 kPa CO2. CA-stored strips showed lower spoilage and dehydration and ion leakage. Storage under 5 kPa O2 þ 5 kPa CO2 was highly effective to maintain the firmness and resistance to bending of the strips. The selected CA caused no alterations in color, acidity, sugars and antioxidants and was effective to maintain lower respiration rate. CA maintained lower counts of mesophilic bacteria, yeasts and molds in red ripe strips.